Elasto-plastic stresses in anisatropic non-homogeneous cylinder - Ghosh, D. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Present investigation is concerned with the elasto-plastic solution of an anisotropic non-homogeneous hollow cylinder. Power law variation has been assumed for all material constant in elastic stage and also for parameters characteristic of the state of anisotropy in plastic yielding. It is observed that plastic yielding may start at the inner surface of the cylinder or at the outer surface and there is a possibility of forming more than one plastic zone depending on the value of constants of the particular material as has been seen in the case of baryte. Numerical results showing distributions of stresses and strains and how the plastic yielding starts in the boron/epoxy cylinder are presented in tabular from.